2021
DOI: 10.26786/1920-7603(2020)609
|View full text |Cite
|
Sign up to set email alerts
|

Testing Pollination Syndromes in <i>Oenothera</i> (Onagraceae)

Abstract: Pollinators are considered a major selective force in shaping the diversification of angiosperms. It has been hypothesized that convergent evolution of floral form has resulted in “pollination syndromes” - i.e. suites of floral traits that correspond to attraction of particular pollinator functional groups. Across the literature, the pollination syndrome concept has received mixed support. This may be due to studies using different methods to describe floral traits and/or the pollination syndrome concept being… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 77 publications
0
4
0
1
Order By: Relevance
“…We recorded diurnal insect visitation on each flower for approximately 1 h using high‐definition video cameras (Sony, San Diego, CA, USA) during pollinator activity (08:00–16:00 hours) on warm, sunny days, capturing a total of 130 h of film. We note that although many Oenothera species are visited by both diurnal and nocturnal floral visitors, the importance of these groups as pollinators varies across species (Rhodes et al, 2017 ; Antoń and Denisow, 2018 ; Krakos and Austin, 2021 ). Prior work has demonstrated that O. fruticosa is visited by diurnal pollinators including, butterflies, bees, and beetles, with no record of nocturnal visitors (Primack and Silander, 1975 ; Silander and Primack, 1978 ; Krakos and Austin, 2021 ).…”
Section: Methodsmentioning
confidence: 93%
See 1 more Smart Citation
“…We recorded diurnal insect visitation on each flower for approximately 1 h using high‐definition video cameras (Sony, San Diego, CA, USA) during pollinator activity (08:00–16:00 hours) on warm, sunny days, capturing a total of 130 h of film. We note that although many Oenothera species are visited by both diurnal and nocturnal floral visitors, the importance of these groups as pollinators varies across species (Rhodes et al, 2017 ; Antoń and Denisow, 2018 ; Krakos and Austin, 2021 ). Prior work has demonstrated that O. fruticosa is visited by diurnal pollinators including, butterflies, bees, and beetles, with no record of nocturnal visitors (Primack and Silander, 1975 ; Silander and Primack, 1978 ; Krakos and Austin, 2021 ).…”
Section: Methodsmentioning
confidence: 93%
“…We note that although many Oenothera species are visited by both diurnal and nocturnal floral visitors, the importance of these groups as pollinators varies across species (Rhodes et al, 2017 ; Antoń and Denisow, 2018 ; Krakos and Austin, 2021 ). Prior work has demonstrated that O. fruticosa is visited by diurnal pollinators including, butterflies, bees, and beetles, with no record of nocturnal visitors (Primack and Silander, 1975 ; Silander and Primack, 1978 ; Krakos and Austin, 2021 ). From the video footage, we identified pollinators and determined pollinator visitation rates of each, only considering insects that were observed contacting the reproductive structures of the flowers.…”
Section: Methodsmentioning
confidence: 93%
“…Os polinizadores são atraídos pelos recursos primários oferecidos pelas flores como pólen, néctar e óleos, e por recursos secundários como a coloração das estruturas florais e seus odores (Endress, 1994). Esses recursos ofertados fazem parte dos atributos florais de grupos vegetais não relacionados, que se adaptaram evolutivamente para atrair determinados tipos de agentes polinizadores e afastar outros, procurando garantir o sucesso de sua reprodução, fenômeno esse investigado pelos botânicos com o objetivo de obter possíveis explicações para melhor compreendê-los (Barônio et al, 2016;Gomes e Quirino, 2016;Lóz et al, 2019;Krakos & Austin, 2020;Kar et al, 2021;Stevenson et al, 2022).…”
Section: Introductionunclassified
“…Studies evaluating the predictability of pollination syndromes have found variable results. For instance, several studies have found that pollination syndromes are partially predictable (they are met for some of the species studied, but not for others), and their predictability varies among habitats (Abrahamczyk et al, 2017; Gómez et al, 2014; Krakos & Austin, 2020; Martén‐Rodríguez et al, 2009; Ollerton et al, 2009; Pérez et al, 2006; Wester & Claßen‐Bockhoff, 2011; Zhang et al, 2005). Moreover, it has been found that pollination syndromes are usually predictable for plant species pollinated by bats, birds, and bees (Armbruster et al, 2011; Ashworth et al, 2015; Bestea et al, 2019; Cortés‐Flores et al, 2017; Danieli‐Silva et al, 2012; Hargreaves et al, 2004; Lázaro et al, 2008; Martén‐Rodríguez et al, 2009; Muchhala, 2003, 2006; Murúa & Espíndola, 2015; Pauw, 2006), and, less frequently, by flies (Rosas‐Guerrero et al, 2014), but not by other groups of animals.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, it has been found that pollination syndromes are usually predictable for plant species pollinated by bats, birds, and bees (Armbruster et al, 2011; Ashworth et al, 2015; Bestea et al, 2019; Cortés‐Flores et al, 2017; Danieli‐Silva et al, 2012; Hargreaves et al, 2004; Lázaro et al, 2008; Martén‐Rodríguez et al, 2009; Muchhala, 2003, 2006; Murúa & Espíndola, 2015; Pauw, 2006), and, less frequently, by flies (Rosas‐Guerrero et al, 2014), but not by other groups of animals. Likewise, it has been found that the predictability of pollination syndromes is increased when pollinators, instead of floral visitors, are used in the analysis (Armbruster et al, 2011; Danieli‐Silva et al, 2012; Hargreaves et al, 2004; Krakos & Austin, 2020; Lázaro et al, 2008; Murúa & Espíndola, 2015; Pauw, 2006; Strakosh & Ferguson, 2005).…”
Section: Introductionmentioning
confidence: 99%